Effect of Ultrasonic Shot Peening on Surface Microstructure and Fatigue Behavior of Structural Alloys - Singh V.; Pandey V.; Kumar S.; Srinivas N.C.S.; Chattopadhyay K. (My University, 2025)
Fatigue resistance of structural materials is considered as one of the most important factors in design of structural components for integrity, efficiency and safe functioning under repeated mechanical/thermal loading. Fatigue resistance of structural alloys is characterized in terms of appropriate parameters based on high cycle/low cycle fatigue loading. Fatigue life comprises of two components, number of cycles for crack initiation and for crack propagation. While there is dominant role of the process of crack initiation in high cycle fatigue, low cycle fatigue is controlled by crack propagation. Invariably, fatigue cracks initiate from the surface and surface modification has been used for enhancement of fatigue life, delaying the process of crack initiation. Inducement of compressive residual stress in surface region through shot peening has been one of the most widely used conventional process of enhancing high cycle fatigue life. This paper presents the effect of surface grain refinement, using the novel technique of ultrasonic shot peening, on enhancement of fatigue life of structural alloys at low stress/strain. © 2015, The Indian Institute of Metals - IIM.